2013
DOI: 10.1038/eye.2013.201
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography findings in spinocerebellar ataxia-3

Abstract: Purpose To report optical coherence tomography (OCT) findings in order to detect subclinical alterations of the afferent visual pathways in spinocerebellar ataxia 3 (SCA-3). Patients and methods Nine genetically confirmed patients (18 eyes) were evaluated with a complete ophthalmologic examination including visual acuity, colour vision, visual field test, and retinal nerve fibre layer (RNFL) and macular thickness with OCT Cirrus HD. A neurological examination was performed and the Scale for the Assessment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
39
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 16 publications
6
39
2
Order By: Relevance
“…Alternatively, they may reflect life-threatening central nervous system (CNS) or systemic pathology, such as retinal microvascular changes or optic disc swelling in papilloedema. Although not tested with the SPECTRALIS FLEX module, standard table-top OCT and OCTA have been used in a range of relevant conditions, including raised intracranial pressure, neurodegenerative diseases and dementia 14–17. Additionally, the retinal vasculature exhibits autoregulation to systemic insults such as hypoxia and has demonstrated quantifiable reductions in vessel density during hypoxic provocation 18 19.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, they may reflect life-threatening central nervous system (CNS) or systemic pathology, such as retinal microvascular changes or optic disc swelling in papilloedema. Although not tested with the SPECTRALIS FLEX module, standard table-top OCT and OCTA have been used in a range of relevant conditions, including raised intracranial pressure, neurodegenerative diseases and dementia 14–17. Additionally, the retinal vasculature exhibits autoregulation to systemic insults such as hypoxia and has demonstrated quantifiable reductions in vessel density during hypoxic provocation 18 19.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies has analyzed intra-retinal layer thickness of the macula. It is important to note that Pula et al and Alvarez et al reported a correlation between disease severity and pRNFL thinning for SCA-ATXN2 and SCA-ATXN3 or SCA-ATXN3 alone [26,34], but data were limited to small sample sizes. Both studies did not report visual acuity for their cohort.…”
Section: Discussionmentioning
confidence: 97%
“…However, with the increasing number of observations of retinal changes in patients with neuroinflammatory and neurodegenerative diseases (Alvarez et al. ; Lange et al. ; Marziani et al.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal imaging devices were primarily developed for the detection of retinal disorders in ophthalmology (Puliafito et al 1995;Jaffe & Caprioli 2004). However, with the increasing number of observations of retinal changes in patients with neuroinflammatory and neurodegenerative diseases (Alvarez et al 2013;Lange et al 2013;Marziani et al 2013;Simao 2013), such devises have also gained importance for neurological diseases (Ziemssen & Ziemssen 2013).…”
Section: Introductionmentioning
confidence: 99%